EFL STUDENTS' PERSPECTIVES ON USING ChatGPT IN WRITING - Nur Salsabila; Warsidi; Sulviana (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2026)
This study aims to explore EFL students’ perspectives on the use of ChatGPT in writing tasks. The research employs a qualitative descriptive method, with data collected through questionnaires and semi-structured interviews. The participants consisted of undergraduate students from the English Education Department, who actively engaged with ChatGPT to support their academic writing. The findings reveal two main aspects: 1) Perceived Usefulness, where students acknowledged that ChatGPT helps them generate ideas, improve vocabulary, and enhance sentence structures and Perceived Ease of Use, as most students found the platform accessible, user-friendly, and supportive in completing writing tasks; and 2) Challenges, which include issues such as Information Literacy, Reproduction Literacy and Socio-Emotional Literacy. Overall, students demonstrated positive perceptions of ChatGPT as a supplementary tool in their writing process. However, they also encountered challenges in managing information, reproducing content, and dealing with socio-emotional aspects. Therefore, teacher guidance and students’ critical evaluation are still essential to ensure effective and responsible use of ChatGPT in academic writing.